A new titanosaur (Dinosauria, Sauropoda) from the Upper Cretaceous of Lo Hueco (Cuenca, Spain). (31st December 2016) - Díez Díaz, V.; Mocho, P.; Páramo, A.; Escaso, F.; Marcos-Fernández, F.; Sanz, J.L.; Ortega, F.
Abstract: The upper Campanian-lower Maastrichtian site of Lo Hueco (Cuenca, Spain) has provided a set of well-preserved partial skeletons in anatomical connection or with a low dispersion of their skeletal elements. One partial skeleton is herein described and a new titanosaurian sauropod is established, Lohuecotitan pandafilandi . This titanosaur is diagnosed by eight autapomorphic features: dorsally and ventrally widened or bifurcated posterior centrodiapophyseal lamina in anterior and middle dorsal vertebrae; short postspinal lamina with a transversely expanded distal end represented by smooth scars in the dorsal vertebrae; anteriormost caudals with the medial spinoprezygapophyseal and medial spinopostzygapophyseal laminae ventrally connected with the prespinal and postspinal laminae, respectively; anterior caudal neural spines with a dorsal projection of the prespinal and postspinal laminae; anterior caudal neural spines bears a "greek-cross"-like cross-section; middle caudal centra having two round and rough structures in the dorsal edge of the posterior articulation, which extends to the dorsal surface of the centrum; the articular ends of the rami of the haemal arches are divided in two articular surfaces; and tuberosity between the anterior and the lateral trochanter of the fibula. The herein performed phylogenetic analysis considered L. pandafilandi as a member of Lithostrotia more derived than Malawisaurus . The known palaeodiversity of the Late Cretaceous Ibero-Armorican titanosaurs is increasing, and further analyses focused on this group will be necessary to better understand the evolutionary history of European titanosaurs and to clarify their relationships within Titanosauria.